ANALISIS KINERJA KEUANGAN PT TRANSPOWER MARINE TBK SEBELUM DAN SESUDAH MELAKUKAN PENAWARAN UMUM PERDANA / INITIAL PUBLIC OFFERING (IPO) TAHUN 2011-2015 - Johannes Baptista Widi (Business Administration Department - Universitas Katolik Parahyangan, 2022)
This research attempted to analyze financial performance of PT Trans Power Marine TBK that made initial public offering (IPO) in 2013. The research was done by analyzing the 5 years financial reports (2011-2015) and later compared the company’s financial performance before and after initial public offering (IPO).This research took a descriptive-analysis method. Financial reports were analyzed using financial ratios well known as relative valuation, while difference in financial performance analyzed using non-parametric statistical method “Wilcoxon”.The result from data processing and ratio analysis showed us a degradation in Trans Power Marine’s financial performance. The fact was strengthen by the result of statistical test that show us there was a difference in company’s financial performance before and after initial public offering (IPO)In the last section of this research, a recommendation to keep monitoring company’s performance is given for the company. Keywords – Financial Performance, Financial Ratio, Initial Public Offering, IPO